How some bilingual pre-school children negotiate their play - Tan, Siew Kuang Rachel (Journal of Modern Languages, 2017)
Play routines are often recognised as important contexts of the interpretation as well as production of actions in studies of child discourse. Participation in peer group activities has also been said to have a positive influence on children’s acquisition of a second language. In this study, some Malaysian pre-school children were observed as they played different games. The real language that they used, specifically those during procedures for entering play activities were recorded and analysed. While most previous research has focused on individual "access strategies" and their outcomes for group participation, the focus of this study is on the collaborative work in such interactions as children attempt to control play.